PENGARUH PENGGUNAAN SMARTPHONE TERHADAP AKTIFITAS KEHIDUPAN SISWA (Studi Kasus MAN 1 Rengat Barat) - Rahmah, Afifah; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Smartphone is a mobile phone that has a high rate capability, which is almost like a computer. The us of smartphones seems to be a need for all leves of society, including teenagers, for teenagers smartphone has a positive impact and negative. The problem in this research are : 1. How do student understanding of smartphpone of the smartphone ? 2. How can the impact of smartphone on student ? 3. How is the level of students adaptation of smartphone users the apliying the theory Evereet Rogers? The purpose of this research is to determind the impact of mobile phone use among student. Population and sample in this studi was a class XI grader uses a smartphone with data collection questioner and technic using descriptive qualitative interviews. The research in results impact especially among students therefore all parties are expected to further supervise the use of telecommunications anything against teenagers.Keywords : Telecommunication, Smartphone, Actifity